Efecto de fertilizantes foliares en la resistencia a la Pyricularia grisea en Arroz (Oryza sativa) bajo riego, variedad Capirona, en Morales - Pérez Flores, Darvin (2003)
In order to find a new alternative for the preventive control of Pyricularia grisea in rice cultivar Capirona variety, a comparative trial with a mixture of foliar fertilizers (Microsul sulfur + Zinc Chelates, Top Cop + Zinc Chelates, Releaf + Stabilizer With a chemical control (Edifenfos 500 EC + Propineb 70% PM) and an absolute control in the Lower May San Martín Region. The experiment was carried out in a slightly alkaline (clay - loam) soil. Under the design of blocks completely random (D.B.C.A) with 6 treatments and 4 replicates. The fertilizers were applied in mixture and in different vegetative period of the crop. The first two treatments (T 1 and T 2) were applied in two stages of development of the plant, macollo and at the beginning of the cotton spot; The T 3 and T 4 were applied in three moments: Macollo, beginning of the cotton point and embedding, and the T s was applied: Macollo, at the beginning of the cotton point and at the beginning of the ear. The best treatment for the control of Pyricularia was T4 (Microsul sulfur + Zinc Chelates at 3.0 lt / Ha + 0.6 kg / Ha respectively), which satisfactorily controlled Pirycularia grisea. The best yields were obtained from T4 Microsul sulfur + Zinc chelates at doses of 3.0 Lt / Ha + 0.6 kg / Ha) with 7918.50 kg / Ha of paddy rice when confronted with the control (Ts). Which obtained 7257.00 kg / ha